Assessing the influence that sports sponsorships has on the purchasing behavior of adult consumers in Metro Manila - Arceo, Rafael Enrico Lao (Animo Repository, 2022)
The Philippines has one of the biggest love for sports in Asia, this is why the research group felt the necessity to further research on the topic, especially that there is a lack of studies regarding sports businesses here in the country. The researchers wanted to assess the impact of sports sponsorship on sports viewers here in Metro Manila, Philippines as it would provide a better understanding of what these consumers look for in products associated with sports. The study focused on the topics of Purchase Behavior and Sports Sponsorship as they believe that these variables would associate well on how this type of demographic would perceive the use of sports sponsorship. Purposive sampling was utilized in the study for gathering data from respondents, and a statistical spreadsheet, jamovi was utilized to analyze the data. Interviews with employees from KidSports, which is a retail store here in the country. From the results gathered, it can be said that the sports sponsorship has a significant impact on the purchasing behavior of sports viewers here in Metro Manila. Keywords: Sports Sponsorship, Purchasing Behavior, Philippines, Sports viewers, sports, purposive sampling, interviews, jamovi